Timber Harvesting Does Not Increase Fire Risk and Severity in Wet Eucalypt Forests of Southern Australia. Issue 4 (19th September 2013) - Attiwill, P.M.; Ryan, M.F.; Burrows, N.; Cheney, N.P.; McCaw, L.; Neyland, M.; Read, S.
Abstract Lindenmayer et al. proposed that logging makes "some kinds of forests more prone to increased probability of ignition and increased fire severity." The proposition was developed most strongly in relation to the wet eucalypt forests of south‐eastern Australia. A key argument was that logging in wet forests results in drier forests that tend to be more fire‐prone, and this argument has gained prominence both in the literature and in policy debate. We find no support for that argument from considerations of eucalypt stand development, and from reanalysis of the only Australian study cited by Lindenmayer et al. In addition, there is no evidence from recent megafires in Victoria that younger regrowth (<10 years) burnt with greater severity than older forest (>70 years); furthermore, forests in reserves (with no logging) did not burn with less severity than multiple‐use forests (with some logging). The flammability of stands of different ages can be explained in terms of stand structure and fuel accumulation, rather than as a dichotomy of regrowth stands being highly flammable but mature and old‐growth stands not highly flammable. Lack of management of fire‐adapted ecosystems carries long‐term social, economic, and environmental consequences.